2018
DOI: 10.1029/2018jc014052
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Chlorophyll‐A in Case II Waters: A Novel Approach With Improved Accuracy Over Widely Implemented Turbid Water Indices

Abstract: A new semianalytical algorithm was formulated to retrieve chlorophyll‐a (CHL) in optically complex waters using in situ data set of coastal waters of eastern Arabian Sea. The algorithm was derived using CHL index of the form, x = (Rrs(λ1)−1−Rrs(λ2)−1) × Rrs(λ3). The first wavelength (λ1) represents the secondary peak of CHL, while the second wavelength (λ2) and third wavelength (λ3) were delineated using a radiative transfer model and partial derivative analysis of hyperspectral remote sensing reflectance, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 90 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…In the range 350-500 nm, all the leaf samples under study are manifesting some low reflectance coefficient (RC) of approximately 5 %. This is not surprising, since the chlorophyll-a and chlorophyll-b absorption peaks are respectively appearing at wavelengths of 440 and 460 nm [9,11,12,[19][20][21][22]. Rapid increase in reflectivity of the leaf samples under study is observed in the range of 490-520 nm values [11].…”
Section: Spectroscopy Diffused Reflection Vegetation Indices Leavementioning
confidence: 70%
“…In the range 350-500 nm, all the leaf samples under study are manifesting some low reflectance coefficient (RC) of approximately 5 %. This is not surprising, since the chlorophyll-a and chlorophyll-b absorption peaks are respectively appearing at wavelengths of 440 and 460 nm [9,11,12,[19][20][21][22]. Rapid increase in reflectivity of the leaf samples under study is observed in the range of 490-520 nm values [11].…”
Section: Spectroscopy Diffused Reflection Vegetation Indices Leavementioning
confidence: 70%
“…In addition, a bimodal variability of chlorophyll-a concentration during summer monsoon occurs in this region. A new algorithm, Goa University Case II (GUC2), was developed to retrieve chl-a in optically complex waters and its validation with in situ observations from the eastern coastal Arabian Sea is useful for the chlorophyll estimations from this region [79]. GUC2 could identify two appropriate wavelengths for deriving chl-a and it could eliminate the effects of total suspended matter and coloured dissolved organic matter.…”
Section: Primary Productivity Of Mudbanksmentioning
confidence: 99%
“…Band expansion phase. In line with the works of [5,49,50], who utilized band combinations as feature candidates in Chl-a concentration modeling, this phase aims to enrich the spectral information using band combination. The filter's kernel size used in this phase is 1 × 1 × 3, indicating that the convolution is performed in the spectral domain and that spectral enrichment is achieved using linear band combination.…”
Section: Network Structure Of Waternetmentioning
confidence: 99%
“…To obtain fair comparisons, we set the numbers of unknown parameters in WaterNet and the feedforward neural networks to be almost the same. The number of neurons in the input, hidden, and output layers of the three feedforward networks are (16,264,1), (16,70,50,1), and (16,44,44,44,1), respectively; whereas the numbers of unknowns are 4753, 4791, and 4753, respectively, as shown in Table 6. The proposed two-stage training is applied to WaterNet and the feedforward neural networks for a fair comparison.…”
Section: Comparison Between Waternet and Feedforward Neural Networkmentioning
confidence: 99%